Comparison of the characteristics of hot tap water scalds and other scalds in Germany. Issue 3 (May 2020) - Schulz, Alexandra; Grigutsch, Daniel; Alischahi, Azar; Perbix, Walter; Daniels, Marc; Fuchs, Paul Christian; Schiefer, Jennifer Lynn
Highlights: We demonstrated the characteristics of hot tap water scalds in Germany. Hot water scalds are associated with a greater total body surface area than other scalds. They also lead to longer ICU stays and worse outcomes than other scald types. It is important to introduce a statutory maximum temperature in domestic buildings. Abstract: Background/aim: Mortality associated with hot tap water scalds remains significant, owing to a lack of up-to-date regulations on tap water temperature. We aimed to evaluate the effect of hot tap water scalds on patients admitted to our adult burn intensive care unit (BICU), and compare them to those with other scald types. Methods: We enrolled patients treated for scalds at the BICU of Cologne-Merheim Medical Center from 1989 to 2014, and retrospectively analyzed their age, sex-specific differences, characteristics, length of hospital stay, number of operations, and mortality. Patients were categorized into two groups: patients with hot tap water scalds and those with all other types of scalds. Results: A total of 333 patients were enrolled. In 23.4% (n = 78) of the cases, the scalds were associated with hot tap water. Such injuries were more commonly observed in older men than women. Hot tap water scalds involved a significantly higher total burned surface area (TBSA) than other scalds, with TBSA values of 24.0% and 15.9% for men, and 21.8% and 10.9% for women, respectively. Hot tap water scald patients had a greater number of surgeries and longer BICU stays (27.8 days vs 9.1 days), and significantly higher mortality values (30.8% (n = 24) vs 4.7% (n = 12)) than those with the other scald types. Conclusions: Hot water scalds are associated with large TBSAs, long stays in the BICU, and worse outcomes compared to the other scald types.